2023
DOI: 10.1038/s41467-023-36324-3
|View full text |Cite
|
Sign up to set email alerts
|

An updated suite of viral vectors for in vivo calcium imaging using intracerebral and retro-orbital injections in male mice

Abstract: Genetically encoded Ca2+ indicators (GECIs) are widely used to measure neural activity. Here, we explore the use of systemically administered PHP.eB AAVs for brain-wide expression of GECIs and compare the expression properties to intracerebrally injected AAVs in male mice. We show that systemic administration is a promising strategy for imaging neural activity. Next, we establish the use of EE-RR- (soma) and RPL10a (Ribo) soma-targeting peptides with the latest jGCaMP and show that EE-RR-tagged jGCaMP8 gives r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…However, to our knowledge no previous studies have demonstrated retinotopic and orientation-selective responses at the single-neuron level or the high-fidelity trial-to-trial responses achievable with intravenous injections of AAV-PhP.eB-Synapsin-GCaMP7s. Even the most recent soma-targeting AAV-PhP.eB-GCaMP8 study examined visual cortical responses to orientation and direction selective stimuli by intracranial injection of the AAV, not intravenous injection (Grodem et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, to our knowledge no previous studies have demonstrated retinotopic and orientation-selective responses at the single-neuron level or the high-fidelity trial-to-trial responses achievable with intravenous injections of AAV-PhP.eB-Synapsin-GCaMP7s. Even the most recent soma-targeting AAV-PhP.eB-GCaMP8 study examined visual cortical responses to orientation and direction selective stimuli by intracranial injection of the AAV, not intravenous injection (Grodem et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In all past studies examining AAV-PhP.B- and AAV-PhP.eB-mediated GCaMP, the maximum post-injection period examined was 10 weeks (Allen et al, 2017; Hillier et al, 2017; Michelson et al, 2019; Brown et al, 2021; Grodem et al, 2023). We have extended this timeframe by demonstrating that expression remains stable and free of nuclear labeling for at least 34 weeks after transduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, neuropil contamination could be reduced by expression of soma restricted calcium sensors. 141,142 In addition, simultaneous imaging of multiple cell types could be achieved by restricting sensors to readily differentiable cellular compartments, such as axons and soma. Finally, imaging of apical dendrites could allow access to deep cortical neurons, an approach used to support population imaging in macaques.…”
Section: Imaging In Cellular Compartmentsmentioning
confidence: 99%